Prevalence of and factors associated with self-reported high blood pressure in Brazilian adults - Malta, Deborah Carvalho; Bernal, Regina Tomie Ivata; Andrade, Silvânia Suely Caribé de Araújo; Silva, Marta Maria Alves da; Velasquez-Melendez, Gustavo (Revista de Saúde Pública, 2017)
OBJECTIVE To analyze factors associated with self-reported high blood pressure among adults in Brazilian state capitals. METHODS The study uses data from Sistema de Vigilância de Fatores de Risco e Proteção para Doenças Crônicas por Inquérito Telefônico (Vigitel – Surveillance System of Risk and Protection Factors of Noncommunicable Diseases by Telephone Survey) collected in 2013. Prevalence rates and their respective 95% confidence intervals by gender were estimated according to sociodemographic variables, lifestyle, reported noncommunicable diseases and self-rated health status. Multivariate logistic regression modeling was used to identify variables associated with self-reported high blood pressure with α < 0.05. RESULTS Prevalence of self-reported high blood pressure among adults living in Brazilian state capitals and the Federal District was 24.1%. The following variables were associated with self-reported high blood pressure: age group, taking 18-24 as reference (all age groups presented increased risk – from 25-34 years [OR = 2.6; 95%CI 2.0–3.4] up to 65 years or more [OR = 28.1; 95%CI 21.7–36.4]); low education level (9 to 11 years of study [OR = 0.8; 95%CI 0.7–0.9] and 12 years or more [OR = 0.6; 95%CI 0.6–0.7]); Black race or skin color (OR = 1.3; 95%CI 1.1–1.5); being a former smoker (OR = 1.2; 95%CI 1.1–1.3); obesity (OR = 2.7; 95%CI 2.4–3.0); diabetes (OR = 2.9; 95%CI 2.5–3.5%), and high cholesterol (OR = 1.9; 95%CI 1.8–2.2). CONCLUSIONS Approximately one quarter of the adult population living in Brazilian state capitals reported having high blood pressure. Information from Vigitel is useful to monitor high blood pressure and identity its associated factors, supporting public policies for health promotion, surveillance and care.